Association of Clinicopathological Factors with Radiation Induced Oral Mucositis in Patients with Head and Neck Carcinoma - Uzma Zareef; Afifa Razi; Rehan Imad; Atif Iqbal (KARACHI MEDICAL AND DENTAL COLLEGE, 2022)
Objective: To evaluate the association of clinicopathological factors with radiation induced oral mucositis in patients with head and neck carcinoma . Methodology This cross sectional study was conducted at  Department of Neurospine and Cancer Institute,  Inclusion criteria were patients with confirmed non-metastatic carcinoma histologically, age range of > 20 and  70 years, patients requiring radical radiotherapy showing visible oral and oropharyngeal mucosa in the field of radiation (55 to 66 Gray). The exclusion criteria were: history of more than one tumour recurrence; prior history of radiation to the head and neck region; atypical liver and renal function; unusual haematological status; other deliberated medical conditions. Non-probability convenience sampling was used for  assesment of oral mucositis. Data was analysed by using SPSS version 23. Results:                                                 A total of 30 patients were included. The mean age was 43 years (25-70 years) and 76.7% were males. Right sided buccul mucosa was most common primary tumor site, 70%  cases belongs to middle-class families with 90%  has no previous family history. Histological grade 2 and grade 2 and grade 3 mucositis was mostly reported. Tobacco chewing and betel nut chewing is the most common habit. The most common site affected is  buccul mucosa, followed by the cheek and tongue. It has been observed that TNM staging and histological grading have shown significance in cases of oral mucositis. Conclusion: This study concludes that the oral mucositis is significantly associated with TNM staging and   histological grading of tumors. Male gender, elderly age, middle to low socioeconomic status,  tobacco and betal nut chewing , right sided buccal mucosa and stage II TNM staging. Grade 2 and grade 3 oral mucositis was  the most frequent clinicopathological factors associated with the development of head and neck cancer. Although previous family is not very frequent in our study population.